2022
DOI: 10.3389/fmicb.2022.816091
|View full text |Cite
|
Sign up to set email alerts
|

The Coupling Between Cell Wall Integrity Mediated by MAPK Kinases and SsFkh1 Is Involved in Sclerotia Formation and Pathogenicity of Sclerotinia sclerotiorum

Abstract: The plant pathogenic fungus Sclerotinia sclerotiorum can survive on a wide range of hosts and cause significant losses on crop yields. FKH, a forkhead box (FOX)-containing protein, functions to regulate transcription and signal transduction. As a transcription factor (TF) with multiple biological functions in eukaryotic organisms, little research has been done on the role of FKH protein in pathogenic fungi. SsFkh1 encodes a protein which has been predicted to contain FOX domain in S. sclerotiorum. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
3
16
0
Order By: Relevance
“…Cell wall integrity was involved in the formation of sclerotia ( Cong et al, 2022 ), and SsAGM1 was involved in the maintenance of cell wall integrity and chitin synthesis. This suggested that SsAGM1 may be involved in vegetative growth, especially the formation of sclerotia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell wall integrity was involved in the formation of sclerotia ( Cong et al, 2022 ), and SsAGM1 was involved in the maintenance of cell wall integrity and chitin synthesis. This suggested that SsAGM1 may be involved in vegetative growth, especially the formation of sclerotia.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that cell wall integrity was related closely to vegetative growth and sclerotia formation of S. sclerotiorum . In S. sclerotiorum , SsFkh1 is involved in the maintenance of cell wall integrity, and SsFkh1 deletion mutants are severely defective in hyphal growth and sclerotia formation ( Cong et al, 2022 ). SsAGM1 was required for chitin synthesis, and it contributed to maintain the integrity of the cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent research, vegetative development and sclerotial production in S. sclerotiorum are intimately tied to cell wall integrity. SsFkh1 contributes to cell wall integrity, and the deletion mutants are significantly deficient in hyphal development and sclerotial formation [ 96 ]. SsAGM1 has been isolated from several fungi, identified as necessary for chitin production, and known to play a role in preserving the integrity of cell wall [ 97 , 98 ].…”
Section: An Array Of Genes Regulating Growth Development and Virulencementioning
confidence: 99%
“…Although parallel S. cerevisiae MAPK cascades in S. sclerotiorum were identified through homology comparison with yeast, few were characterized molecularly (Hegedus et al, 2016). The disruption of the cell wall integrity MAPK pathway components, including Pkc1, Bck1, Mkk1, and Smk3, not only led to decreased cell wall integrity, but also decreased sclerotia formation and virulence (Bashi et al, 2016; Cong et al, 2022). Likewise, deletion of the MAPKKK gene Ssos4 , a component of the high osmolarity MAPK pathway associated with mitigating hyperosmotic stressors, led to reduced sclerotia formation and virulence (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%